Forecast for container liftings based on vessel calls measures to be taken should the number be lower or higher than actual / Zahariah Ahmad - Ahmad, Zahariah (1998)
This research deals with the techniques of estimating future container liftings for export purposes. The major aim of this research is to find a suitable method of forecasting to apply in practice. This research also focuses on determining the factors involved in forecasting container liftings and identifying the problems arising when the forecast is higher or lower than actual. Each chapter of this research is intended to provide information, understanding and skill in achieving accurate forecasting of container liftings. The proposal of this research is offered in Chapter 1 which introduces the nature of forecasting container liftings in Green Peninsula Agencies, the objectives of this research, the recent problems in forecasting, hypothesis, methodology and the scope of this research. Chapter 2 describes the background of the company and discuss the relevant literature review. Chapter 3 discusses the function of forecasting container liftings, factors affecting container liftings and also deals with the observation of Green Peninsula's market share in the shipping industry. Chapter 4 deals with general methods of forecasting that use in market. The next three chapters continue from Chapter 4 but these three chapters indicate the techniques of forecasting in detail which can give us a good result of forecasting. Chapter 8 analyses the techniques introduced earlier in Chapter 4. Finally, Chapter 9 develops the recommendations for the findings, where mathematical technique is better than descriptive forecasting. Included in this chapter is a discussion on improving the method of forecasting.